Religious Moderation and Environmental Challenges in Northeastern Nigeria - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Babangida, Bala; Badikko, Muazu (Program Pascasarjana UNU Surakarta, 2026)
Northeastern Nigeria faces a countless of environmental challenges, including desertification, deforestation, water scarcity, and the adverse effects of climate change. These issues not only threaten the region’s ecological balance but also jeopardize the livelihoods, health, and social stability of its communities. Amidst these challenges, religious moderation emerges as a pivotal factor in fostering sustainable environmental stewardship. This paper explores the intersection of religious moderation and environmental management, emphasizing the influential role of religious leaders and Islamic teachings in promoting eco-friendly practices. Utilizing a mixed-methods approach, including qualitative interviews with community leaders and quantitative analysis of environmental indicators, the study identifies key mechanisms through which religious moderation contributes to mitigating environmental degradation. Findings reveal that religious leaders who advocate for balance, stewardship (Khilafah), and justice (Adl) significantly enhance community engagement in conservation efforts and the adoption of sustainable agricultural practices. Additionally, case studies highlight successful initiatives where religious institutions collaborated with governmental and non-governmental organizations to address water scarcity and reforestation. However, the research also identifies challenges such as poverty, limited educational resources, and the rise of extremism that hinder the full potential of religious moderation in environmental governance. The paper concludes by recommending a collaborative framework between religious bodies, government agencies, and local communities to amplify the impact of religious moderation on environmental sustainability. By integrating religious principles with environmental policies, Northeastern Nigeria can navigate its ecological challenges more effectively, ensuring a harmonious balance between development and conservation. This study contributes to the broader discourse on the role of religion in environmental sustainability and provides actionable insights for policymakers and religious leaders aiming to foster a resilient and sustainable future for the region.